2015
DOI: 10.2146/ajhp150032
|View full text |Cite
|
Sign up to set email alerts
|

ASHP national survey of pharmacy practice in hospital settings: Dispensing and administration—2014

Abstract: Health-system pharmacists continue to have a positive impact on improving healthcare through programs that improve the efficiency, safety, and clinical outcomes of medication use in health systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
123
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 15 publications
(62 reference statements)
1
123
0
3
Order By: Relevance
“…In addition to the local standards of Saudi Center of healthcare accreditation. 12,14,[18][19][20]24,25 The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient's education, Pharmacy inventory control and stock management, Pharmacy education and training, and pharmacy total quality management. The 5-point Likert response scale system closed and ended questions used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the local standards of Saudi Center of healthcare accreditation. 12,14,[18][19][20]24,25 The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient's education, Pharmacy inventory control and stock management, Pharmacy education and training, and pharmacy total quality management. The 5-point Likert response scale system closed and ended questions used.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies conducted to explore the pharmacy practice including clinical pharmacy activities in different counties. [12][13][14][15] Other studies surveyed with clinical pharmacy services or per medication services with clinical pharmacy service provided. 16,17 Also, some studies published explore that is in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into eight domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditatio in addition to the local standards of Saudi Center of healthcare accreditation. [1][2][3][4][5][6][7] The parts were pharmacy management and resources, prescribing and medication control, preparation of medications and dispensing, Computerized and pharmacy technology, clinical pharmacy services, drug monitoring and patient's education, Pharmacy inventory control and stock management, Pharmacy education and training. The 5-point Likert response scale system was used with closed and ended questions.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Several studies published overall the world showed the implementation of pharmacy computerized and automation at hospital pharmacies among pharmacy practice through either international or local studies. [3][4][5][6][7][8] Some studies focused on clinical pharmacy services and acute care section. [9][10] Other investigation emphasized on pharmacy automation and technology or pharmacy informatics.…”
Section: Introductionmentioning
confidence: 99%